2017
DOI: 10.1080/07391102.2017.1344568
|View full text |Cite
|
Sign up to set email alerts
|

Novel urushiol derivatives as HDAC8 inhibitors: rational design, virtual screening, molecular docking and molecular dynamics studies

Abstract: Three series of novel urushiol derivatives were designed by introducing a hydroxamic acid moiety into the tail of an alkyl side chain and substituents with differing electronic properties or steric bulk onto the benzene ring and alkyl side chain. The compounds' binding affinity toward HDAC8 was screened by Glide docking. The highest-scoring compounds were processed further with molecular docking, MD simulations, and binding free energy studies to analyze the binding modes and mechanisms. Ten compounds had Glid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
21
0

Year Published

2018
2018
2025
2025

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 34 publications
(21 citation statements)
references
References 45 publications
0
21
0
Order By: Relevance
“…Our research results have suggested that the binding pattern of urushiol derivative ligands such as ligand compound 4 to the HDAC2 receptor [ 23 , 24 ] could be detected by the molecular docking technique. We attained the HDAC2 X-ray crystal structure (PDB no.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Our research results have suggested that the binding pattern of urushiol derivative ligands such as ligand compound 4 to the HDAC2 receptor [ 23 , 24 ] could be detected by the molecular docking technique. We attained the HDAC2 X-ray crystal structure (PDB no.…”
Section: Resultsmentioning
confidence: 99%
“…Notably, our research has indicated that the urushiol derivatives have a remarkable binding affinity with good scoring of histone deacetylase (HDAC)2 and HDAC8 [ 23 , 24 ]. Histone deacetylases (HDACs) are a group of zinc metalloenzymes that regulate chromatin remodeling and gene transcription by catalyzing the removal of an acetyl group moiety from the Ɛ-amino groups of the lysine residues on the amino terminal tails of the core histones [ 25 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The structure elucidation of (−)-eriodictyol (4), (−)-dihydroquercetin (5), and (−)-fustin (6) were determined by Infrared spectroscopy (IR), NMR, and electronic circular dichroism analysis as described in the previous report. 6…”
Section: Fisetin (7)mentioning
confidence: 99%
“…[2][3][4] Some urushiol derivatives have been evaluated as histone deacetylase 8 (HDAC8) inhibitors by molecular docking study. 5 Recently, we have reported the chemical constituents from the twigs and the flowers of this plant. 6,7 To the best of our knowledge, no compounds from the root of this plant have been reported.…”
mentioning
confidence: 99%